1992
DOI: 10.1177/40.6.1316915
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural immunogold localization of prostaglandin endoperoxide synthase (cyclooxygenase) to non-membrane-bound cytoplasmic lipid bodies in human lung mast cells, alveolar macrophages, type II pneumocytes, and neutrophils.

Abstract: Lipid bodies are non-membrane-bound, lipid-rich cytoplasmic inclusions that occur in many mammalian cell types. Because lipid bodies are more prominent in cells associated with inflammation and are repositories of arachidonylphospholipids, a role for lipid bodies in the oxidative metabolism of arachidonic acid to form eicosanoids has been suggested. To evaluate further whether lipid bodies, in addition to serving as non-membranous sources of substrate arachidonate, are involved in eicosanoid formation, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
89
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 1 publication
9
89
0
1
Order By: Relevance
“…However, some morphological studies show the presence of proteins, including soluble ones, in the LD core (Dvorak et al 1992;Bozza et al 1997;Robenek et al 2004Robenek et al , 2005. It is not plausible that hydrophilic proteins exist alone in the core, but amphiphilic proteins may complex with phospholipids to make structures compatible with the hydrophobic environment.…”
Section: Structure Of Lipid Dropletsmentioning
confidence: 99%
“…However, some morphological studies show the presence of proteins, including soluble ones, in the LD core (Dvorak et al 1992;Bozza et al 1997;Robenek et al 2004Robenek et al , 2005. It is not plausible that hydrophilic proteins exist alone in the core, but amphiphilic proteins may complex with phospholipids to make structures compatible with the hydrophobic environment.…”
Section: Structure Of Lipid Dropletsmentioning
confidence: 99%
“…By using immunocytochemistry at the light level and ultrastructural postembedding immunogold, cyclooxygenase has been reported to localize at eosinophil lipid bodies, both in naturally formed lipid bodies in eosinophils from HES patients and in PAF-induced lipid bodies (Dvorak et al 1992, 1993, Bozza et al 1997. Previous studies on the intracellular localization of 5-LO have shown that 5-LO localization is cell type-specific and also varies according to the activation state of the cell.…”
Section: Leukocyte Lipid Body Functions In Inflammationmentioning
confidence: 99%
“…By using immunocytochemistry at the light level and ultrastructural postembedding immunogold, cyclooxygenase has been reported to localize at eosinophil lipid bodies, both in naturally formed lipid bodies in eosinophils from HES patients and in PAF-induced lipid bodies (Dvorak et al 1992. Previous studies on the intracellular localization of 5-LO have shown that 5-LO localization is cell typespecific and also varies according to the activation state of the cell (Rouzer & Kargman 1988, Reid et al 1990, Woods et al 1993, Brock et al 1994).…”
Section: Localization Of Eicosanoid-forming En-zymes To Human Eosinopmentioning
confidence: 99%
“…Together our findings support a role for lipid bodies to function as specific sites for eicosanoid formation. The compartmentalization of arachidonate substrate (Weller et al 1989(Weller et al , 1991, cPLA 2 , and eicosanoid-forming enzymes (Dvorak et al 1992) provides in one locale an efficient mean to regulate arachidonate release and directly couple it with the enzymes to form eicosanoids.…”
Section: Localization Of Eicosanoid-forming En-zymes To Human Eosinopmentioning
confidence: 99%